Central banking and financialization : a Romanian account of how Eastern Europe became subprime - Gabor, Daniela (Basingstoke : Palgrave Macmillan, 2011)
This book explores the causes and effects of the rise of neoliberalism in Eastern Europe in the aftermath of the collapse of the Soviet Union. It provides a political economy analysis of the role of central banks, and identifies them as a key actor in the production and dissemination of the neoliberal economic policies.
Includes bibliographical references (p. 235-250) and index.
oif 16/09/14
Loan
Keywords: Banks and banking, Central -- Europe, Eastern; Neoliberalism -- Europe, Eastern; Subprime mortgage loans -- Europe, Eastern; Europe, Eastern -- Economic policy -- 1989-; Decommunization -- Economic aspects -- Europe, Eastern